Economical and green biodiesel production process using river snail shells-derived heterogeneous catalyst and co-solvent method. (June 2016) - Roschat, Wuttichai; Siritanon, Theeranun; Kaewpuang, Teadkait; Yoosuk, Boonyawan; Promarak, Vinich
Graphical abstract: Highlights: River snail shells-derived CaO catalyst was synthesized for the first time. 98.5% FAME yield was achieved in 90 min under the use 10% v/v of THF in methanol. The transesterification reaction mechanism is experimentally demonstrated. The co-solvent method of THF/methanol successfully decreases activation energy of reaction. Abstract: River snail shells-derived CaO was used as a heterogeneous catalyst to synthesize biodiesel via transesterification of palm oil with methanol. The shell materials were calcined in air at 600–1000 °C for 3 h. Physicochemical properties of the resulting catalysts were characterized by TGA–DTG, XRD, SEM, BET, XRF, FT-IR and TPD. CaO catalyzed transesterification mechanism of palm oil into biodiesel was verified. The effects of adding a co-solvent on kinetic of the reaction and %FAME yield were investigated. %FAME yield of 98.5% ± 1.5 was achieved under the optimal conditions of catalyst/oil ratio of 5 wt.%; methanol/oil molar ratio of 12:1; reaction temperature of 65 °C; 10% v/v of THF in methanol and reaction time of 90 min. The results ascertained that river snail shells is a novel raw material for preparation of CaO catalyst and the co-solvent method successfully decreases the reaction time and biodiesel production cost.